Clinical Aspects of Dermatitis Associated with Dirofilaria repens in Pets: A Review of 100 Canine and 31 Feline Cases (1990–2010) and a Report of a New Clinic Case Imported from Italy to Dubai - Walter Tarello (Journal of Parasitology Research)
Cutaneous dirofilariasis is a parasitic disease caused by the mosquito-borne filarial nematodes Dirofilaria (Nochtiella) repens, living in the subcutaneous tissue of dogs, cats, wild carnivores, and humans. Cases have been recently reported also from Germany, Czech Republic, Hungary, Ukraine, Russia, Austria, Switzerland, France, The Netherlands, and the Middle East. D. repens is not widely known to cause chronic pruritic dermatitis in animals. Dermatological signs observed in 100 canine clinic cases were pruritus (100%), erythema (79%), papulae (62%), focal or multifocal alopecia (55%), hyperkeratosis (18%), crusting (14%), nodules (12%), acantosis (5%), and eczema (3%). Signs other than dermatological were conjunctivitis (46%), anorexia (35%), vomiting (26%), fever (25%), lethargy (20%), and lymph-adenomegaly (10%). A case imported from Italy to Dubai is described. The opportunistic role of D. repens might explain the presence of asymptomatic carriers, the concurrent observation of nondermatological signs, and the development of dermatitis in a subgroup of parasitized dogs.